Comparison of Changes in Cortisol Values Before and After Administration of a Combination of Continuous Fentanyl and Paracetamol Drip in Post-Craniotomy Patients in ICU of Haji Adam Malik General Hospital Medan - Etania, Cassandra; Irina, Rr Sinta; Ihsan, Muhammad (Jurnal Neuroanestesi Indonesia, 2024)
Introduction: Post-craniotomy surgical pain can trigger an inflammatory response and release various stress response mediators. Prolonged stress response to pain can increase cortisol secretion which will eventually be resulted in cortisol dysfunction and widespread inflammation. Opioids have been shown to provide pain management after craniotomy. Fentanyl is a commonly used opioid analgesic to manage postoperative pain. The addition of paracetamol is often used as multimodal analgesia which aims to reduce postoperative pain and to minimize the stress response that occurs. The aim of the study was to obtain a comparison of changes in cortisol values before and after the administration of a combination of continuous fentanyl and paracetamol in post-craniotomy patients in the ICU of Haji Adam Malik General Hospital Medan. Subject and Methods: This research design used a cross sectional test with pretest and posttest design, with primary data sources obtained directly from examinations on patients in the ICU. This study involved 15 post-craniotomy patients in the ICU with mechanical ventilation. The cortisol levels in the patients blood were checked before and after administration continuous fentanyl and paracetamol drip. Results: There was a decrease in cortisol levels after being given a combination of continuous fentanyl and paracetamol drip in post-craniotomy patients by 18% with a p-value of 0.001 (p